Radical acceptance eaudiobook Embracing your life with the heart of a buddha. - Brach, Tara (Tantor Media, 2012)
"Believing that something is wrong with us is a deep and tenacious suffering," says Tara Brach at the start of this illuminating book. This suffering emerges in crippling self-judgments and conflicts in our relationships, in addictions and perfectionism, in loneliness and overwork—all the forces that keep our lives constricted and unfulfilled. Radical Acceptance offers a path to freedom, including the day-to-day practical guidance developed over Dr. Brach's twenty years of work with therapy clients and Buddhist students. Writing with great warmth and clarity, Tara Brach brings her teachings alive through personal stories and case histories, fresh interpretations of Buddhist tales, and guided meditations. Step by step, she leads us to trust our innate goodness, showing how we can develop the balance of clear-sightedness and compassion that is the essence of Radical Acceptance. Radical Acceptance does not mean self-indulgence or passivity. Instead it empowers genuine change: healing fear and shame and helping to build loving, authentic relationships. When we stop being at war with ourselves, we are free to live fully every precious moment of our lives.